Lateral inhibition in the somatosensory cortex during and between migraine without aura attacks: Correlations with thalamocortical activity and clinical features. (May 2016) - Coppola, Gianluca; Bracaglia, Martina; Di Lenola, Davide; Iacovelli, Elisa; Di Lorenzo, Cherubino; Serrao, Mariano; Evangelista, Maurizio; Parisi, Vincenzo; Schoenen, Jean; Pierelli, Francesco
Background: We studied lateral inhibition in the somatosensory cortex of migraineurs during and between attacks, and searched for correlations with thalamocortical activity and clinical features. Participants and methods: Somatosensory evoked potentials (SSEP) were obtained by electrical stimulation of the right median (M) or ulnar (U) nerves at the wrist or by simultaneous stimulation of both nerves (MU) in 41 migraine without aura patients, 24 between (MO), 17 during attacks, and in 17 healthy volunteers (HVs). We determined the percentage of lateral inhibition of the N20–P25 component by using the formula [(100)–MU/(M + U)*100]. We also studied high-frequency oscillations (HFOs) reflecting thalamocortical activation. Results: In migraine, both lateral inhibition (MO 27.9% vs HVs 40.2%; p  = 0.009) and thalamocortical activity (MO 0.5 vs HVs 0.7; p  = 0.02) were reduced between attacks, but not during. In MO patients, the percentage of lateral inhibition negatively correlated with days elapsed since the last migraine attack ( r  = −0.510, p  = 0.01), monthly attack duration ( r  = −0.469, p  = 0.02) and severity ( r  = −0.443, p  = 0.03), but positively with thalamocortical activity ( r  = −0.463, p  = 0.02). Conclusions: We hypothesize that abnormal migraine cycle-dependent dynamics of connectivity between subcortical and cortical excitation/inhibition networks may contribute to clinical features of MO and recurrence of attacks.